Laminate, packaging material and package
The laminate structure with polyethylene or polypropylene layers and inorganic oxide vapor deposition enhances recyclability, heat sealability, and visibility, addressing the challenges of conventional packaging materials.
Patent Information
- Application Number
- JP2023096898
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional packaging materials face challenges in achieving high recyclability, heat sealability, and maintaining content visibility due to the use of multiple resin materials and metal layers that hinder recyclability and visibility.
A laminate structure comprising a base material layer, intermediate layer, and sealant layer, all made of polyethylene or polypropylene, with inorganic oxide vapor deposition layers to enhance heat resistance and visibility, and adhesive layers for bonding, ensuring a recyclability of 90% or more.
The laminate achieves excellent recyclability, heat sealability, and content visibility, with improved heat resistance and barrier properties, suitable for various packaging applications.
Smart Images

Figure 2024178622000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, and a packaging material and a package using the same. More specifically, the present invention relates to a laminate having excellent material recyclability and a small environmental load, and a packaging material and a package using the same. [Background technology]
[0002] Packaging bags are made from a variety of materials and are combined depending on the nature and amount of the contents to be packaged, post-treatment to prevent deterioration of the contents, the form in which the packaging bag is transported, the method of opening the packaging bag, and the method of disposal.
[0003] For example, in a packaging bag for a flexible package using laminated films, a biaxially oriented film such as polypropylene or polyester is used in combination to obtain mechanical strength of the packaging bag, and a sealant film such as polyethylene, polypropylene, or ethylene-vinyl acetate copolymer is used to seal the contents as a packaging bag. In addition, aluminum foil or ethylene-vinyl alcohol copolymer is laminated on the film to prevent deterioration of the contents.
[0004] The laminates using the above-mentioned various functionally separated materials are designed with an emphasis on suitability in each process, from packaging the contents to transportation, storage, and opening. However, due to the increasing awareness of environmental issues in recent years, emphasis has been placed on functions such as resource saving and recyclability of various products, and similar functions are being required for laminates used in packaging bags. Generally, packaging materials that contain 90% or more of the main resin are considered to be highly recyclable, but many conventional packaging materials are composed of multiple resin materials and sometimes paper and metal materials, and do not meet this standard, so they are not currently recycled.
[0005] Patent Document 1 describes an example in which both the substrate and the heat seal layer are made of polyethylene. Such a laminate made of polyethylene or a laminate made of polypropylene, in which the substrate and the heat seal layer are made of the same material, can easily meet the recyclability standard. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2020-517502 Summary of the Invention [Problem to be solved by the invention]
[0007] However, polyethylene film (PE film) and polypropylene film (PP film) have a lower melting point than biaxially oriented polyamide film (ONy film) and biaxially oriented polyester film (PET film), which have been used as base materials in the past, and therefore cannot be heat-sealed at high temperatures during bag making. In order to obtain good heat sealing suitability, the laminate needs to have a structure such as a protective layer to protect the PE film or PP film used as the base material from the heat of heat sealing.
[0008] On the other hand, since the laminate may be required to have good visibility of the contents from the viewpoint of practical use, the protective layer provided on the substrate needs to be one that does not reduce visibility.
[0009] Patent Document 1 proposes providing a metal layer (specifically, an aluminum layer) having an optical density of 1.0 to 3.6 on the substrate in order to impart good barrier properties against oxygen and water vapor to the substrate. However, when such a metal layer is provided, it is difficult to maintain good visibility of the contents. In addition, the metal layer may reduce recyclability.
[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a laminate that is excellent in recyclability, heat sealability, and visibility of the contents. Another object of the present invention is to provide a packaging material and a package using the laminate. [Means for solving the problem]
[0011] One aspect of the present invention includes, for example, the following embodiment. [1] A first inorganic oxide vapor-deposited layer, a base layer, and a sealant layer are laminated in this order, A laminate, wherein the substrate layer and the sealant layer both comprise polyethylene or both comprise polypropylene. [2] The laminate according to [1], further comprising an intermediate layer between the base layer and the sealant layer, wherein the base layer, the intermediate layer and the sealant layer all contain polyethylene, or all contain polypropylene. [3] The laminate according to [1] or [2], wherein the base layer is a biaxially stretched film. [4] The laminate according to [2], further comprising a second inorganic oxide vapor-deposited layer formed on the intermediate layer. [5] The laminate according to [2] or [4], wherein the base layer and the intermediate layer are laminated together via a first adhesive layer, and the intermediate layer and the sealant layer are laminated together via a second adhesive layer, and the second adhesive layer contains a gas barrier adhesive. [6] The laminate according to any one of [1] to [5], wherein the proportion of polyethylene or polypropylene in the laminate is 90 mass % or more. [7] A packaging material comprising the laminate according to any one of [1] to [6]. [8] The packaging material according to [7], which is a standing pouch. [9] A package comprising the packaging material described in [7] or [8] and contents contained in the packaging material. Effect of the Invention
[0012] According to the present invention, a laminate excellent in recyclability, heat sealability, and visibility of contents is provided. The present invention also provides a packaging material and a package using the laminate. [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a laminate of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing one embodiment of a laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings where necessary. However, the present invention is not limited to the following embodiments.
[0015] <Laminate> Fig. 1 is a schematic cross-sectional view showing one embodiment of a laminate of the present invention. The laminate 1 shown in Fig. 1 includes a base layer 10, a first adhesive layer 40, an intermediate layer 20, a second adhesive layer 50, and a sealant layer 30. The substrate layer 10 has a first inorganic oxide vapor-deposited layer 11 on its outer surface 10a, and the intermediate layer 20 has a second inorganic oxide vapor-deposited layer 14 on one surface thereof. The substrate layer 10 has a printed layer 12 on its inner surface 10b side, and the intermediate layer 20 has a gas barrier coating layer 15 on the second inorganic oxide vapor-deposited layer 14 thereof. From the viewpoint of recyclability (ease of reforming after melting the resin material), the base layer 10, the intermediate layer 20, and the sealant layer 30 are preferably made of the same material. For example, these layers are all made of polyethylene film or all made of polypropylene film. Each layer will be described below.
[0016] (base material layer) The base layer 10 is a layer containing polyethylene or polypropylene, and may be a layer constituted of a polyethylene film or a polypropylene film. The polyethylene film may be a film containing 70% by mass or more, or 85% by mass or more, of polyethylene, or may be a film containing 100% by mass of polyethylene. The polypropylene film may be a film containing 70% by mass or more, or 85% by mass or more of polypropylene, or may be a film containing 100% by mass of polypropylene.
[0017] Examples of polyethylene include high-density polyethylene (HDPE) from the viewpoints of vapor deposition processing, printing processing, bag making processing, and filling suitability, etc. Also, from the viewpoints of film-forming properties including stretching suitability, impact resistance, and transparency (visibility), examples include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and very low-density polyethylene (VLDPE).
[0018] In order to improve physical properties such as flexibility, a multilayer film such as high density polyethylene (HDPE) / medium density polyethylene (MDPE) / low density polyethylene (LDPE) / medium density polyethylene (MDPE) / high density polyethylene (HDPE) formed by a coextrusion method may be used as the base layer 10.
[0019] Examples of polypropylene include homopolymers, random copolymers, block copolymers, terpolymers, etc., and the polymer type can be appropriately selected according to the application and required performance. For example, from the viewpoint of transparency, homopolymers or random copolymers can be used. When the rigidity and heat resistance of the laminate are important, homopolymers can be used, and when impact resistance is important, random copolymers can be used. As polypropylene, biomass-derived polypropylene and mechanically recycled or chemically recycled polypropylene may be used.
[0020] For the purpose of imparting easy adhesion and sealing properties, a multi-layered film may be used as the base layer 10, in which a copolymer or terpolymer is formed as a skin layer by coextrusion on a homopolymer core layer.
[0021] The film constituting the base layer 10 may be a stretched film or a non-stretched film. However, from the viewpoint of impact resistance, heat resistance, water resistance, dimensional stability, etc., the film may be a stretched film. This allows the laminate to be more suitably used in applications where hot filling is performed. The stretching method is not particularly limited, and any method may be used as long as a dimensionally stable film can be provided, such as stretching by inflation, uniaxial stretching, biaxial stretching, etc.
[0022] The thickness of the base layer 10 is not particularly limited. Depending on the application, the thickness can be 6 μm or more and 200 μm or less, but from the viewpoint of obtaining excellent impact resistance and excellent gas barrier properties, the thickness may be 9 μm or more and 50 μm or less, or 12 μm or more and 38 μm or less.
[0023] The film constituting the base layer 10 may be subjected to various pretreatments such as corona treatment, plasma treatment, and flame treatment in order to improve adhesion to the first inorganic oxide vapor deposition layer.
[0024] The film constituting the base layer 10 may contain antiblocking agents, antioxidants, UV absorbers, antistatic agents, flame retardants, inorganic fillers, organic fillers, dyes, pigments, etc., within the scope of not impairing the intended performance as a base layer.
[0025] (First inorganic oxide vapor deposition layer) The first inorganic oxide vapor-deposited layer 11 is provided to prevent defects during heat sealing during bag making or filling and sealing, and to ensure heat sealing suitability. Specifically, it can suppress appearance defects such as wrinkles that occur when the base material layer 10 comes into contact with a heat seal bar, and adhesion (removal) of the base material layer 10 to the heat seal bar due to thermal welding. The first inorganic oxide vapor-deposited layer 11 imparts heat resistance to the base material layer 10, and may be provided as the outermost layer of the laminate 1.
[0026] The first inorganic oxide deposition layer 11 may be, for example, a deposition layer made of an inorganic oxide (metal oxide) such as aluminum oxide, silicon oxide, magnesium oxide, or tin oxide. From the viewpoint of transparency and barrier properties, the inorganic oxide may be selected from the group consisting of aluminum oxide, silicon oxide, and magnesium oxide. Furthermore, from the viewpoint of cost, the inorganic oxide may be selected from aluminum oxide and silicon oxide. From the viewpoint of excellent tensile stretchability during processing, the first inorganic oxide deposition layer 11 is more preferably a layer containing silicon oxide. By using the first inorganic oxide deposition layer 11, it is possible to impart heat resistance to the base layer 10 with a very thin layer that does not affect the recyclability of the laminate 1 and the visibility of the contents.
[0027] When silicon oxide is selected as the first inorganic oxide deposition layer 11, the O / Si ratio is preferably 1.7 or more. When the O / Si ratio is 1.7 or more, the content of dangling bonds of silicon atoms is suppressed, and good transparency is easily obtained. In addition, the O / Si ratio is preferably 2.0 or less. When the O / Si ratio is 2.0 or less, the crystallinity of SiO is high, which can prevent the deposition layer from becoming too hard, and good tensile strength is obtained. From the viewpoint of obtaining these effects more fully, the O / Si ratio is preferably 1.75 to 1.9, and more preferably 1.8 to 1.85.
[0028] When aluminum oxide is selected as the first inorganic oxide vapor-deposited layer 11, the O / Al ratio is preferably 1.4 or more. When the O / Al ratio is 1.4 or more, the content of dangling bonds of aluminum atoms is suppressed, and good transparency is easily obtained. In addition, the O / Al ratio is preferably 1.7 or less. When the O / Al ratio is 1.7 or less, the crystallinity of AlO becomes high, which prevents the vapor-deposited layer from becoming too hard, and good tensile resistance is obtained. From the viewpoint of obtaining these effects more fully, the O / Al ratio is preferably 1.4 or more and 1.7 or less, and more preferably 1.5 or more and 1.55 or less.
[0029] The thickness of the first inorganic oxide vapor deposition layer is preferably 5 nm or more and 50 nm or less. When the thickness is 5 nm or more, sufficient heat resistance can be imparted to the base layer. When the thickness is 50 nm or less, the layer is prevented from cracking due to deformation caused by internal stress, and the deterioration of heat resistance can be suppressed, and recyclability and visibility of contents can be easily maintained. From this viewpoint, the thickness is more preferably 10 nm or more or 20 nm or more, and more preferably 40 nm or less or 35 nm or less.
[0030] The thickness of the laminate is changed according to the weight of the contents to be packaged. When packaging light contents, it is generally made thin in consideration of cost, and when packaging heavy contents, it is generally made thick in consideration of strength. As the thickness of the laminate increases, the amount of heat required to thermally melt the heat seal surface of the sealant layer increases. For this reason, it is preferable to change the thickness of the first inorganic oxide deposition layer 11 in proportion to the total thickness of the laminate. It is preferable that the ratio of the thickness of the first inorganic oxide deposition layer 11 to the total thickness of the laminate is 0.001% or more and 0.1% or less. When this ratio is 0.001% or more, the desired heat resistance is easily obtained and better heat sealability can be obtained, and when it is 0.1% or less, waste of the material of the first inorganic oxide deposition layer 11 can be suppressed while maintaining recyclability and visibility of the contents, and an increase in the amount of heat required for heat sealing can be suppressed.
[0031] The first inorganic oxide deposition layer 11 can be formed, for example, by vacuum film formation. In the vacuum film formation, physical vapor deposition or chemical vapor deposition can be used. Examples of physical vapor deposition include, but are not limited to, vacuum deposition, sputtering, and ion plating. Examples of chemical vapor deposition include, but are not limited to, thermal CVD, plasma CVD, and photo CVD.
[0032] In the vacuum film formation, resistance heating vacuum deposition, EB (Electron Beam) heating vacuum deposition, induction heating vacuum deposition, sputtering, reactive sputtering, dual magnetron sputtering, plasma enhanced chemical vapor deposition (PECVD), etc. are particularly preferably used. However, in terms of productivity, the vacuum deposition method is superior. As the heating means for the vacuum deposition method, it is preferable to use any one of the electron beam heating method, resistance heating method, and induction heating method.
[0033] When the first inorganic oxide deposition layer 11 is formed on the base material layer 10, an anchor coat layer, which will be described later, may be formed on the base material layer 10. Furthermore, for the purpose of protecting the first inorganic oxide deposition layer 11, an overcoat layer may be formed on the first inorganic oxide deposition layer 11. The overcoat layer may be formed using a material that is particularly excellent in heat resistance from among the materials for forming the gas barrier coating layer, which will be described later. Furthermore, from the viewpoints of slipperiness and printability, the overcoat layer may be formed using a matte varnish or the like.
[0034] (Printing layer) The printed layer 12 can be formed on the substrate layer 10 on the side opposite to the outer surface 10a on which the first inorganic oxide vapor deposition layer 11 is formed, that is, on the inner surface 10b on which the intermediate layer 20 is laminated. The method for forming the printed layer 12 (image) is not particularly limited, and the printed layer 12 can be formed by ordinary gravure printing or flexographic printing using an appropriate ink. As the ink, there are solvent-based inks and water-based inks, but it is preferable to use water-based inks from an environmental perspective. In addition, the inner surface 10b of the substrate layer 10 may be subjected to a surface treatment such as a corona treatment or a plasma treatment in order to improve the adhesion of the printed layer 12.
[0035] (Middle class) The intermediate layer 20 is a layer containing polyethylene or polypropylene, and may be a layer constructed from a polyethylene film or a polypropylene film. The polyethylene film may be a film containing 70% by mass or more, or 85% by mass or more, of polyethylene, or may be a film containing 100% by mass of polyethylene. The polypropylene film may be a film containing 70% by mass or more, or 85% by mass or more of polypropylene, or may be a film containing 100% by mass of polypropylene.
[0036] Examples of polyethylene include high-density polyethylene (HDPE) from the viewpoints of vapor deposition processing, printing processing, bag making processing, and filling suitability, etc. Also, from the viewpoints of film-forming properties including stretching suitability, impact resistance, and transparency (visibility), examples include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and very low-density polyethylene (VLDPE).
[0037] In order to improve physical properties such as flexibility, a multi-layer film such as high density polyethylene (HDPE) / medium density polyethylene (MDPE) / low density polyethylene (LDPE) / medium density polyethylene (MDPE) / high density polyethylene (HDPE) formed by a coextrusion method may be used as the intermediate layer 20.
[0038] Examples of polypropylene include homopolymers, random copolymers, block copolymers, terpolymers, etc., and the polymer type can be appropriately selected according to the application and required performance. For example, from the viewpoint of transparency, homopolymers or random copolymers can be used. When the rigidity and heat resistance of the laminate are important, homopolymers can be used, and when impact resistance is important, random copolymers can be used. As polypropylene, biomass-derived polypropylene and mechanically recycled or chemically recycled polypropylene may be used.
[0039] For the purpose of imparting easy adhesion and sealing properties, the intermediate layer 20 may be a multi-layered film in which a copolymer or terpolymer is formed as a skin layer by coextrusion on a homopolymer core layer.
[0040] The film constituting the intermediate layer 20 may be a stretched film or a non-stretched film. However, from the viewpoint of impact resistance, heat resistance, water resistance, dimensional stability, etc., the film may be a stretched film. This allows the laminate to be more suitably used in applications where hot filling is performed. The stretching method is not particularly limited, and any method may be used as long as a dimensionally stable film can be supplied, such as stretching by inflation, uniaxial stretching, biaxial stretching, etc.
[0041] The thickness of the intermediate layer 20 is not particularly limited. Depending on the application, the thickness can be 9 μm or more and 50 μm or less, but is preferably 12 μm or more and 35 μm or less, and more preferably 12 μm or more and 30 μm or less. By making the thickness of the intermediate layer 20 9 μm or more, the strength and heat resistance of the laminate can be improved, and by making the thickness of the intermediate layer 20 50 μm or less, the processability of the laminate can be improved.
[0042] The film constituting the intermediate layer 20 may be subjected to various pretreatments such as corona treatment, plasma treatment, and flame treatment in order to improve adhesion to the second inorganic oxide vapor deposition layer and the like.
[0043] The film constituting the intermediate layer 20 may contain antiblocking agents, antioxidants, ultraviolet absorbers, antistatic agents, flame retardants, inorganic fillers, organic fillers, dyes, pigments, etc., within the scope of not impairing the intended performance as an intermediate layer.
[0044] (Second inorganic oxide vapor deposition layer) In the laminate 1, a second inorganic oxide vapor-deposited layer 14 may be formed on at least one surface of the intermediate layer 20. In this embodiment, the second inorganic oxide vapor-deposited layer 14 is formed on the surface of the intermediate layer 20 facing the second adhesive layer 50, but it may be formed on the opposite surface. The second inorganic oxide vapor-deposited layer 14 imparts oxygen barrier properties and water vapor barrier properties to the laminate 1.
[0045] The configuration of the second inorganic oxide deposited layer 14 is as described in the section for the first inorganic oxide deposited layer 11. By using the second inorganic oxide deposited layer 14, high barrier properties can be obtained with a very thin layer that does not affect the recyclability of the laminate 1.
[0046] When silicon oxide is selected as the second inorganic oxide deposition layer 14, the O / Si ratio is preferably 1.7 or more. When the O / Si ratio is 1.7 or more, the content ratio of dangling bonds of silicon atoms is suppressed, and good transparency is easily obtained. In addition, the O / Si ratio is preferably 2.0 or less. When the O / Si ratio is 2.0 or less, the crystallinity of SiO is high, and the deposition layer can be prevented from becoming too hard, and good tensile resistance can be obtained. In addition, when the O / Si ratio is 2.0 or less, it is easy to follow the shrinkage of the film, and the deterioration of the barrier property can be suppressed. From the viewpoint of obtaining these effects more fully, the O / Si ratio is preferably 1.75 to 1.9, and more preferably 1.8 to 1.85.
[0047] When aluminum oxide is selected as the second inorganic oxide deposition layer 14, the O / Al ratio is preferably 1.4 or more. When the O / Al ratio is 1.4 or more, the content ratio of dangling bonds of aluminum atoms is suppressed, and good transparency is easily obtained. In addition, the O / Al ratio is preferably 1.7 or less. When the O / Al ratio is 1.7 or less, the crystallinity of AlO is high, and the deposition layer can be prevented from becoming too hard, and good tensile resistance can be obtained. In addition, when the O / Al ratio is 1.7 or less, it is easy to follow the shrinkage of the film, and the deterioration of the barrier property can be suppressed. From the viewpoint of obtaining these effects more fully, the O / Al ratio is preferably 1.4 to 1.7, and more preferably 1.5 to 1.55.
[0048] The thickness of the deposition layer made of aluminum oxide is preferably 5 nm or more and 30 nm or less. When the thickness is 5 nm or more, sufficient gas barrier properties can be obtained. When the thickness is 30 nm or less, cracks caused by deformation due to internal stress of the thin film can be suppressed, and the deterioration of gas barrier properties can be suppressed. Note that, when the thickness exceeds 30 nm, the cost is likely to increase due to an increase in the amount of material used and a prolonged film formation time, and is therefore not preferable from an economical point of view. From the same viewpoint as above, the thickness of the deposition layer is more preferably 7 nm or more and 15 nm or less.
[0049] The thickness of the vapor deposition layer made of silicon oxide is preferably 10 nm or more and 50 nm or less. When the thickness is 10 nm or more, sufficient gas barrier properties can be obtained. When the thickness is 50 nm or less, cracks caused by deformation due to internal stress of the thin film can be suppressed, and the deterioration of gas barrier properties can be suppressed. Note that, when the thickness exceeds 50 nm, the cost is likely to increase due to an increase in the amount of material used and a prolonged film formation time, and is therefore not preferable from an economical point of view. From the same viewpoint as above, the thickness of the vapor deposition layer is more preferably 20 nm or more and 40 nm or less.
[0050] The method for forming the second inorganic oxide deposited layer 14 is as described in the section for the first inorganic oxide deposited layer 11.
[0051] (Anchor coat layer) A known anchor coating agent may be used to form an anchor coating layer on the surface of the intermediate layer 20 on which the second inorganic oxide deposition layer 14 is formed. This can improve the adhesion of the deposition layer made of inorganic oxide. Examples of anchor coating agents include polyester polyurethane resins, polyether polyurethane resins, and acrylic urethane resins. From the viewpoints of heat resistance and interlayer adhesive strength, polyester polyurethane resins are preferred.
[0052] A polyvinyl alcohol resin may be used as the anchor coating agent. The polyvinyl alcohol resin may be any resin having a vinyl alcohol unit formed by saponifying a vinyl ester unit, such as polyvinyl alcohol (PVA) or ethylene-vinyl alcohol copolymer (EVOH).
[0053] When a polyvinyl alcohol-based resin is used as the anchor coating agent, the method for forming the anchor coating layer includes coating using a polyvinyl alcohol-based resin solution, multilayer extrusion, etc. In the case of multilayer extrusion, lamination may be performed via an adhesive resin such as maleic anhydride-grafted modified polyethylene.
[0054] (Gas barrier coating layer) For the purpose of improving the gas barrier property and protecting the second inorganic oxide deposition layer 14, a gas barrier coating layer 15 may be provided on the second inorganic oxide deposition layer 14. Although not particularly limited, the gas barrier coating layer 15 may contain a hydroxyl group-containing polymer compound, and specifically, may be a heat-dried product of a composition containing at least one of a hydroxyl group-containing polymer compound and a hydrolysate thereof, and at least one selected from the group consisting of a metal alkoxide, a silane coupling agent, and a hydrolysate thereof.
[0055] The gas barrier coating layer 15 can be formed using a composition (hereinafter referred to as an overcoat agent) obtained by adding a hydroxyl-containing polymer compound and a metal alkoxide and / or a silane coupling agent to water or a water / alcohol mixture. The overcoat agent can be prepared by mixing, for example, a solution in which a hydroxyl-containing polymer compound, which is a water-soluble polymer, is dissolved in an aqueous (water or water / alcohol mixture) solvent with a metal alkoxide and / or a silane coupling agent directly or after being previously treated by hydrolysis or the like.
[0056] Examples of the hydroxyl group-containing polymer compound include polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. Among these, polyvinyl alcohol (PVA) is preferred because it has particularly excellent gas barrier properties when used as an overcoat agent for the gas barrier coating layer.
[0057] The metal alkoxide includes a compound represented by the following general formula (I). M(OR 1 ) m (R 2 ) n-m …(I) In the above general formula (I), R 1 and R 2are each independently a monovalent organic group having 1 to 8 carbon atoms, and are preferably an alkyl group such as a methyl group or an ethyl group. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n. 1 or R 2 If there are multiple, R 1 R 2 They may be the same or different.
[0058] Specific examples of metal alkoxides include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc. Tetraethoxysilane and triisopropoxyaluminum are preferred because they are relatively stable in aqueous solvents after hydrolysis.
[0059] The silane coupling agent includes a compound represented by the following general formula (II). Si(OR 11 ) p (R 12 ) 3-p R 13 …(II) In the above general formula (II), R 11 represents an alkyl group such as a methyl group or an ethyl group, and R 12 represents a monovalent organic group such as an alkyl group, an aralkyl group, an aryl group, an alkenyl group, an alkyl group substituted with an acryloxy group, or an alkyl group substituted with a methacryloxy group, and R 13 represents a monovalent organic functional group, and p represents an integer of 1 to 3. 11 or R 12 If there are multiple, R 11 R 12 R may be the same or different. 13 Examples of the monovalent organic functional group represented by the formula (I) include a monovalent organic functional group containing a glycidyloxy group, an epoxy group, a mercapto group, a hydroxyl group, an amino group, an alkyl group substituted with a halogen atom, or an isocyanate group.
[0060] Specific examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.
[0061] The silane coupling agent may also be a polymer formed by polymerizing the compound represented by the general formula (II). The polymer is preferably a trimer, more preferably 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate. This is a condensation polymer of 3-isocyanate alkylalkoxysilane. It is known that the isocyanate moiety of this 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate is chemically non-reactive, but the reactivity is ensured by the polarity of the nurate moiety. In general, it is added to adhesives, etc., in the same manner as 3-isocyanate alkylalkoxysilane, and is known as an adhesion improver. Therefore, by adding 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate to a hydroxyl group-containing polymer compound, the water resistance of the gas barrier coating layer can be improved by hydrogen bonding. 3-isocyanate alkyl alkoxysilanes are highly reactive and have low liquid stability, whereas 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurates are not water-soluble due to the polarity of the nurate moiety, but are easily dispersed in aqueous solutions and can maintain a stable liquid viscosity. In addition, the water resistance of 3-isocyanate alkyl alkoxysilanes is equivalent to that of 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurates.
[0062] 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate may be produced by thermal condensation of 3-isocyanatepropylalkoxysilane, and may contain the raw material 3-isocyanatepropylalkoxysilane, but this is not a problem. More preferably, it is 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate, and even more preferably, it is 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate. This methoxy group has a fast hydrolysis rate, and those containing a propyl group are relatively inexpensive and therefore 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate is advantageous in practical use.
[0063] The amount of the metal alkoxide in the overcoat agent can be 1 to 4 parts by mass, or may be 2 to 3 parts by mass, per part by mass of the hydroxyl-containing polymeric compound, from the viewpoint of maintaining adhesion to the deposition layer and gas barrier properties. Similarly, the amount of the silane coupling agent can be 0.01 to 1 part by mass, or may be 0.1 to 0.5 parts by mass, per part by mass of the hydroxyl-containing polymeric compound. When a silane compound (alkoxysilane) is used as the metal alkoxide, the amount of the silane compound (metal alkoxide and silane coupling agent) in the overcoat agent can be 1 to 4 parts by mass, or may be 2 to 3 parts by mass, per part by mass of the hydroxyl-containing polymeric compound.
[0064] If necessary, known additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity adjuster, a colorant, etc. may be added to the overcoat agent within a range that does not impair the gas barrier property.
[0065] The overcoating agent can be applied by, for example, a dipping method, a roll coating method, a gravure coating method, a reverse gravure coating method, an air knife coating method, a comma coating method, a die coating method, a screen printing method, a spray coating method, a gravure offset method, etc. The coating film obtained by applying the overcoating agent can be dried by, for example, a hot air drying method, a hot roll drying method, a high frequency irradiation method, an infrared irradiation method, a UV irradiation method, or a combination thereof.
[0066] The temperature at which the coating film is dried can be, for example, 50 to 150° C., and is preferably 70 to 100° C. By keeping the drying temperature within the above range, the occurrence of cracks in the deposition layer or gas barrier coating layer can be further suppressed, and excellent barrier properties can be exhibited.
[0067] The gas barrier coating layer may be formed using an overcoat agent containing a hydroxyl group-containing polymer compound (e.g., polyvinyl alcohol resin) and a silane compound. The overcoat agent may contain an acid catalyst, an alkali catalyst, a photopolymerization initiator, etc., as necessary.
[0068] Examples of the silane compound include a silane coupling agent, polysilazane, and siloxane. Specific examples of the silane compound include tetramethoxysilane, tetraethoxysilane, glycidoxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, and hexamethyldisilazane.
[0069] The thickness of the gas barrier coating layer is preferably 50 to 1000 nm, and more preferably 100 to 500 nm. If the thickness of the gas barrier coating layer is 50 nm or more, there is a tendency that more sufficient gas barrier properties can be obtained, and if it is 1000 nm or less, there is a tendency that sufficient flexibility can be maintained.
[0070] (Sealant layer) The sealant layer 30 is made of a material having a lower melting point than the material constituting the base layer 10 and has heat sealability. The sealant layer 30 is a layer containing polyethylene or polypropylene, and may be a layer made of a polyethylene film or a polypropylene film. The polyethylene film may be a film containing 70% by mass or more, or 85% by mass or more, of polyethylene, or may be a film containing 100% by mass of polyethylene. The polypropylene film may be a film containing 70% by mass or more, or 85% by mass or more of polypropylene, or may be a film containing 100% by mass of polypropylene.
[0071] As the polyethylene, linear low density polyethylene (LLDPE) can be used. Also, for the purpose of imparting rigidity, a film having a co-extruded laminated structure in which the intermediate layer 20 side is made of high density polyethylene (HDPE) or medium density polyethylene (MDPE) and the heat seal side is made of low density polyethylene (LDPE) can be used as the sealant layer 30.
[0072] As the polypropylene, polypropylene-based resins such as homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, and propylene-α-olefin copolymer can be used.
[0073] There is no particular limitation on the thickness of the sealant layer 30. The thickness can be set to 30 μm or more and 150 μm or less depending on the weight of the contents, the shape of the packaging material, the processability, and the like.
[0074] The film constituting the sealant layer 30 may contain various additives such as flame retardants, slip agents, antiblocking agents, antioxidants, light stabilizers, and tackifiers, as long as the additives do not impair the intended performance of the sealant layer.
[0075] (adhesive layer) The first adhesive layer 40 is a layer containing at least one type of adhesive, and is provided between the base material layer 10 and the intermediate layer 20 to bond them together. When the intermediate layer 20 is not used, the first adhesive layer 40 may be provided between the base material layer 10 and the sealant layer 30 to bond them together. The second adhesive layer 50 is a layer containing at least one type of adhesive, and is provided between the intermediate layer 20 and the sealant layer 30 to bond them together. For example, any adhesive such as a one-component curing type or two-component curing type urethane adhesive can be used for the first adhesive layer 40 and the second adhesive layer 50. In addition, any solvent-based adhesive and any solventless adhesive can be used for the first adhesive layer 40 and the second adhesive layer 50. These adhesives may contain a layered inorganic compound for the purpose of further enhancing the barrier properties.
[0076] The first adhesive layer 40 may be formed using a solvent-free adhesive from the viewpoint of suppressing dimensional changes in the printed image during lamination when a printed layer is provided on the base layer. Examples of the solvent-free adhesive include urethane adhesives, epoxy adhesives, and silicone adhesives, but from the viewpoint of impact resistance, urethane adhesives are preferred, and two-liquid curing urethane adhesives are particularly preferred.
[0077] The two-component curing type urethane-based solventless adhesive contains a polyol component as a base component and a polyisocyanate component as a curing agent.
[0078] The polyol component may be one or a mixture of two or more selected from the group consisting of polyester polyols, polyether polyols, polyether ester polyols, and polyurethane polyols.
[0079] The polyester polyol may be, for example, an ester reaction product of a polycarboxylic acid, a dialkyl ester of a polycarboxylic acid, or a mixture thereof with a glycol-based solvent. The polycarboxylic acid may be, for example, succinic acid, glutaric acid, isophthalic acid, terephthalic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, or dimer acid. The glycol-based solvent may be, for example, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butylene glycol, neopentyl glycol, or 1,6-hexanediol.
[0080] The polyether polyol may be, for example, a polymer of an oxirane compound and a low molecular weight polyol. The oxirane compound may be, for example, ethylene oxide, propylene oxide, butylene oxide, or tetrahydrofuran. The low molecular weight polyol may be, for example, water, ethylene glycol, propylene glycol, trimethylolpropane, or glycerin.
[0081] The polyether ester polyol may be, for example, one obtained by reacting a polyvalent carboxylic acid, a dialkyl ester of a polyvalent carboxylic acid, or a mixture thereof with a polyether polyol.
[0082] The polyurethane polyols may be, for example, the reaction product of polyester polyols, polyether polyols, polyetherester polyols, and polyisocyanate monomers.
[0083] The polyisocyanate component may be an aliphatic polyisocyanate, an aromatic polyisocyanate, and mixtures thereof.
[0084] The aliphatic polyisocyanate may be, for example, a polyisocyanate monomer, a polyisocyanate derivative, or a polyisocyanate-terminated prepolymer. The polyisocyanate monomer may be, for example, tetramethylene diisocyanate, isopropylene diisocyanate, 1,6-hexamethylene diisocyanate, dodecamethylene diisocyanate, or trimethylhexamethylene diisocyanate. The polyisocyanate derivative may be, for example, 1,3-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, lysine diisocyanate, or isophorone diisocyanate.
[0085] The aromatic polyisocyanate may be, for example, a polyisocyanate monomer, a polyisocyanate derivative, or a polyisocyanate-terminated prepolymer. The polyisocyanate monomer may be, for example, tolylene diisocyanate, phenylene diisocyanate, diphenylmethane diisocyanate, naphthalene diisocyanate, xylylene diisocyanate, or tetramethyl xylylene diisocyanate. The polyisocyanate derivative may be, for example, an isocyanurate derived from a polyisocyanate monomer. The polyisocyanate-terminated prepolymer may be a bifunctional polyisocyanate having a terminal isocyanate group obtained by reacting a polyisocyanate monomer with a bifunctional polyol compound such as polypropylene glycol. The polyisocyanate-terminated prepolymer may be a multifunctional polyisocyanate having a terminal isocyanate group obtained by reacting a polyisocyanate monomer with a trifunctional or higher polyol compound such as trimethylolpropane.
[0086] The second adhesive layer 50 may be formed using a solvent-based adhesive from the viewpoint of resistance to the contents. Examples of the solvent-based adhesive include urethane-based adhesives, epoxy-based adhesives, and silicone-based adhesives, but from the viewpoint of impact resistance, urethane-based adhesives are preferred, and two-liquid curing urethane-based adhesives are particularly preferred. The solvent used in the solvent-based adhesive is not particularly limited, and examples thereof include ethyl acetate, methanol, isopropyl alcohol, methyl ethyl ketone, and ethanol.
[0087] The coating weight (weight per unit area) of each adhesive layer is 0.5 g / m 2 More than 3.0g / m 2 Less than 1.0 g / m is preferred. 2 More than 2.0g / m 2 More preferably, the coating weight of the adhesive layer is 0.5 g / m or less. 2 If the coating weight of the adhesive layer is 3.0 g / m or more, the effect of suppressing delamination between layers can be improved. 2 If it is equal to or less than this, it is possible to suppress the occurrence of winding misalignment during processing of the laminate, and it is possible to improve the appearance quality of the laminate, and in addition, appropriate lamination strength is obtained.
[0088] The adhesive may be an adhesive that can exhibit gas barrier properties after curing (gas barrier adhesive). In other words, the adhesive layer may contain a gas barrier adhesive, and may be said to be a cured product of the gas barrier adhesive. In particular, when an adhesive layer that contacts the second inorganic oxide vapor deposition layer is formed with an adhesive that exhibits gas barrier properties, it is possible to further suppress the deterioration of the gas barrier properties due to the occurrence of cracks in the second inorganic oxide vapor deposition layer. This can further improve the gas barrier performance of the laminate 1. Examples of gas barrier adhesives include epoxy adhesives, polyester / polyurethane adhesives, and polyamine adhesives. Specific examples include "Maxive" manufactured by Mitsubishi Gas Chemical Company, Inc. and "Paslim" manufactured by DIC Corporation.
[0089] For example, when the laminate has two layers (a substrate layer and a sealant layer), either a solventless or solvent-based adhesive may be used to bond the two layers. When resistance to contents or barrier properties are required, a solvent-based adhesive or a gas barrier adhesive can be used. For example, if the laminate has three layers (a substrate layer, an intermediate layer, and a sealant layer), a solvent-free adhesive can be used for the first adhesive layer (between the substrate layer and the intermediate layer) and a solvent-based adhesive can be used for the second adhesive layer (between the intermediate layer and the sealant layer).
[0090] The thickness of the first adhesive layer 40 and the second adhesive layer 50 is preferably 0.5 μm or more and 6 μm or less, more preferably 0.8 μm or more and 5 μm or less, and even more preferably 1.0 μm or more and 4.5 μm or less. By making the thickness of the first adhesive layer 40 and the second adhesive layer 50 0.5 μm or more, the adhesiveness of the first adhesive layer 40 and the second adhesive layer 50 can be improved. By making the thickness of the first adhesive layer 40 and the second adhesive layer 50 6 μm or less, the processability of the laminate 1 can be improved.
[0091] The first adhesive layer 40 and the second adhesive layer 50 can be formed by various known methods such as a direct gravure roll coating method, a gravure roll coating method, a kiss coating method, a reverse roll coating method, a Fontaine method, and a transfer roll coating method.
[0092] In the laminate 1 of the present embodiment configured as described above, the base layer 10, the intermediate layer 20, and the sealant layer 30 are all composed of polyethylene or all composed of polypropylene, so that the proportion of polyethylene or polypropylene in the laminate 1 is 90 mass % or more. This gives the laminate 1 high recyclability. The proportion (mass %) of polyethylene or polypropylene in the laminate 1 can be calculated by the following formula (1). (mass of base layer 10+mass of intermediate layer 20+mass of sealant layer 30) / mass of entire laminate 1×100 … (1)
[0093] <Packaging materials> A packaging material (packaging bag) made of the laminate 1 can be formed by folding the laminate 1 so that the sealant layers 30 face each other, or by stacking two laminates 1 with the sealant layers 30 facing each other, and then joining the sealant layers 30 at the periphery by heat sealing while leaving the filled portion for the contents. By performing the above-mentioned joining while sandwiching the folded bottom film, a standing pouch can be formed as the packaging material. In addition, the laminate 1 can be used as various packaging bags such as pillow packaging, four-sided seal, three-sided seal, and gusset bags. In this way, the laminate 1 can be applied to various packaging materials.
[0094] <Package> The package includes the packaging material and a content contained in the packaging material, such as food-based liquid seasonings, beverages, jellies, etc., and non-food-based detergents, shampoos, conditioners, lotions, milky lotions, disinfectants, etc.
[0095] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above embodiments. For example, the laminate may not include one or more of the printed layer, intermediate layer, second inorganic oxide vapor deposition layer, and gas barrier coating layer. When the laminate does not include an intermediate layer, the second adhesive layer is not necessary, and the second inorganic oxide vapor deposition layer may be provided on the substrate layer. When the laminate does not include a gas barrier coating layer, the laminate may be as shown in FIG. 2.
[0096] The laminate 2 shown in Fig. 2 is obtained by removing the gas barrier coating layer 15 from the laminate 1. Instead of removing the gas barrier coating layer 15, the laminate 2 is provided with a second adhesive layer 60 formed using an adhesive (the gas barrier adhesive described above) that can exhibit gas barrier properties after curing. This makes it possible to suppress a decrease in gas barrier properties due to the occurrence of cracks in the second inorganic oxide vapor deposition layer 14. EXAMPLES
[0097] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0098] (Preparation of base layer) The physical properties of the base layers used in each example are shown in Tables 1 and 2. The layer configuration (stacking order) of each layer is as shown in Tables 1 and 2.
[0099] (Preparation of anchor coating agent) Acrylic polyol and tolylene diisocyanate were mixed so that the number of NCO groups in tolylene diisocyanate was equal to the number of OH groups in the acrylic polyol, and diluted with ethyl acetate so that the total solid content (total amount of acrylic polyol and tolylene diisocyanate) was 5 mass%. β-(3,4 epoxycyclohexyl)trimethoxysilane was further added to the diluted mixture so that the amount was 5 mass parts per 100 mass parts of the total amount of acrylic polyol and tolylene diisocyanate, and these were mixed to prepare an anchor coating agent.
[0100] (Preparation of Overcoat Agent) An overcoat agent was prepared by mixing the following liquids A, B and C in a mass ratio of 70 / 20 / 10, respectively. Liquid A: A hydrolysis solution with a solid content of 5 mass% (SiO2 equivalent) obtained by adding 72.1 g of 0.1N hydrochloric acid to 17.9 g of tetraethoxysilane (Si(OC2H5)4) and 10 g of methanol and stirring for 30 minutes. Liquid B: 5% by mass solution of polyvinyl alcohol in water / methanol (mass ratio of water:methanol is 95:5). Liquid C: A hydrolysis solution in which 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate was diluted with a mixture of water and isopropyl alcohol (water:isopropyl alcohol mass ratio 1:1) to a solid content of 5 mass%.
[0101] (Preparation of intermediate film A) A 32 μm-thick unstretched polyethylene film (HDPE film) was prepared, with both sides subjected to corona treatment. The above-mentioned anchor coating agent was applied to one side by gravure coating and dried to provide an anchor coating layer with a thickness of 0.1 μm. Next, a 50 nm-thick transparent deposition layer (second inorganic oxide deposition layer) made of silicon oxide was formed on the anchor coating layer using a vacuum deposition device with electron beam heating. The O / Si ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. Intermediate film A was obtained as described above.
[0102] (Preparation of intermediate film B) A 20 μm-thick biaxially oriented polypropylene film (OPP film) was prepared, with both sides subjected to corona treatment. The above-mentioned anchor coating agent was applied to one side by gravure coating and dried to provide an anchor coating layer with a thickness of 0.1 μm. Next, a 50 nm-thick transparent deposition layer (second inorganic oxide deposition layer) made of silicon oxide was formed on the anchor coating layer by a vacuum deposition device using an electron beam heating method. The O / Si ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. The above-mentioned overcoat agent was applied to the deposition layer by gravure coating and dried to form a 0.3 μm-thick gas barrier coating layer (overcoat layer) having gas barrier function. An intermediate film B was obtained as described above.
[0103] (Preparation of Solvent-Free Adhesive) A solventless adhesive (urethane-based NS adhesive) was prepared by mixing 100 parts by mass of DIC Graphics' Dickdry 2K-SF-220A with 85 parts by mass of DIC Graphics' Dickdry HA-233B while heating at 40°C.
[0104] (Preparation of Solvent-Based Adhesive A) A solvent-based adhesive A (urethane-based DL adhesive), which is a urethane-based adhesive, was prepared by mixing 100 parts by mass of Takelac A525 manufactured by Mitsui Chemicals, Inc., 11 parts by mass of Takenate A52 manufactured by Mitsui Chemicals, Inc., and 84 parts by mass of ethyl acetate.
[0105] (Preparation of Solvent-Based Adhesive B (Gas Barrier Adhesive)) A solvent consisting of ethyl acetate and methanol mixed in a mass ratio of 1:1 was mixed with 23 parts by mass of Maxive C93T manufactured by Mitsubishi Gas Chemical Co., Ltd., and 5 parts by mass of Maxive M-100 manufactured by Mitsubishi Gas Chemical Co., Ltd. to prepare a solvent-based adhesive B (gas barrier adhesive), which is a gas barrier adhesive.
[0106] Example 1 As the substrate layer, a 30 μm-thick unstretched polyethylene film (HDPE film) with both sides corona-treated as shown in Table 1 was prepared. A 40 nm-thick transparent deposition layer (first inorganic oxide deposition layer) made of silicon oxide was formed on the corona-treated outer surface of the substrate layer using a vacuum deposition device with electron beam heating. The O / Si ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. Meanwhile, a printing layer (thickness 1 μm) was formed on the corona-treated inner surface of the substrate layer by gravure printing using a urethane-based ink.
[0107] Next, the surface of the base layer on which the printed layer was formed was adhered to the corona-treated surface of the sealant layer by a dry lamination method using a solvent-free adhesive. The adhesive layer was designated as the first adhesive layer. The thickness of the first adhesive layer was 1.8 μm. As the sealant layer, a 120 μm thick non-oriented polyethylene film (LLDPE) that had been corona-treated on one side was prepared. In this manner, a laminate was obtained.
[0108] Example 2 A transparent deposition layer (first inorganic oxide deposition layer) made of aluminum oxide and having a thickness of 10 nm was formed on the outer corona-treated surface of the base layer by a vacuum deposition device using an electron beam heating method. The O / Al ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. Other than this, the same procedure as in Example 1 was followed to obtain a laminate.
[0109] Example 3 A laminate was obtained in the same manner as in Example 1, except that a biaxially oriented polyethylene film (LLDPE film) having a thickness of 25 μm and having been corona-treated on both sides was prepared as the base layer.
[0110] Example 4 A laminate was obtained in the same manner as in Example 2, except that a biaxially oriented polyethylene film (LLDPE film) having a thickness of 25 μm and having been corona-treated on both sides was prepared as the base layer.
[0111] Example 5 A 20 μm-thick biaxially oriented polypropylene film (OPP film) with both sides corona-treated as shown in Table 1 was prepared as the base layer. A 40 nm-thick transparent deposition layer (first inorganic oxide deposition layer) made of silicon oxide was formed on the corona-treated outer surface of the base layer using a vacuum deposition device with electron beam heating. The O / Si ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. Meanwhile, a printing layer (1 μm thick) was formed on the corona-treated inner surface of the base layer by gravure printing using a urethane-based ink.
[0112] Next, the surface of the base layer on which the printed layer was formed was adhered to the corona-treated surface of the sealant layer by a dry lamination method using a solvent-based adhesive A. This adhesive layer was designated as the first adhesive layer. The thickness of the first adhesive layer was 1.8 μm. As the sealant layer, a 60 μm thick unstretched polypropylene film (CPP) that had been corona-treated on one side was prepared. In this manner, a laminate was obtained.
[0113] Example 6 A transparent deposition layer (first inorganic oxide deposition layer) made of aluminum oxide and having a thickness of 10 nm was formed on the outer corona-treated surface of the base layer by a vacuum deposition device using an electron beam heating method. The O / Al ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. Other than this, the same procedure as in Example 5 was followed to obtain a laminate.
[0114] Comparative Example 1 A laminate was obtained in the same manner as in Example 1, except that the first inorganic oxide vapor deposition layer was not formed.
[0115] Comparative Example 2 A laminate was obtained in the same manner as in Example 3, except that the first inorganic oxide vapor deposition layer was not formed.
[0116] Comparative Example 3 A laminate was obtained in the same manner as in Example 5, except that the first inorganic oxide vapor-deposited layer was not formed.
[0117] Example 7 As the substrate layer, a 30 μm-thick unstretched polyethylene film (HDPE film) with both sides corona-treated as shown in Table 2 was prepared. A 40 nm-thick transparent deposition layer (first inorganic oxide deposition layer) made of silicon oxide was formed on the corona-treated outer surface of the substrate layer using a vacuum deposition device with electron beam heating. The O / Si ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. Meanwhile, a printing layer (thickness 1 μm) was formed on the corona-treated inner surface of the substrate layer by gravure printing using a urethane-based ink.
[0118] Next, the surface of the substrate layer on which the printed layer was formed was bonded to the surface of the intermediate film A on which the vapor deposition layer was not formed by a dry lamination method using a solvent-free adhesive. This adhesive layer was designated as the first adhesive layer. The thickness of the first adhesive layer was 1.8 μm.
[0119] A 120 μm thick non-oriented polyethylene film (LLDPE) that had been corona-treated on one side was prepared as the sealant layer. The surface of intermediate film A on which the deposition layer was formed was bonded to the corona-treated surface of the sealant layer by dry lamination using solvent-based adhesive B as the second adhesive layer. The thickness of the second adhesive layer was 2.1 μm. A laminate was obtained as described above.
[0120] Example 8 A transparent deposition layer (first inorganic oxide deposition layer) made of aluminum oxide and having a thickness of 10 nm was formed on the outer corona-treated surface of the base layer by a vacuum deposition device using an electron beam heating method. The O / Al ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. Other than this, the same procedure as in Example 7 was carried out to obtain a laminate.
[0121] Example 9 A laminate was obtained in the same manner as in Example 7, except that a biaxially oriented polyethylene film (LLDPE film) having a thickness of 25 μm and having been corona-treated on both sides was prepared as the base layer.
[0122] Example 10 A laminate was obtained in the same manner as in Example 8, except that a biaxially oriented polyethylene film (LLDPE film) having a thickness of 25 μm and having been corona-treated on both sides was prepared as the base layer.
[0123] Example 11 A 20 μm-thick biaxially oriented polypropylene film (OPP film) with both sides corona-treated as shown in Table 1 was prepared as the base layer. A 40 nm-thick transparent deposition layer (first inorganic oxide deposition layer) made of silicon oxide was formed on the corona-treated outer surface of the base layer using a vacuum deposition device with electron beam heating. The O / Si ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. Meanwhile, a printing layer (1 μm thick) was formed on the corona-treated inner surface of the base layer by gravure printing using a urethane-based ink.
[0124] Next, the surface of the substrate layer on which the printed layer was formed was adhered to the surface of the intermediate film B on which the gas barrier coating layer was not formed by a dry lamination method using a solvent-based adhesive A. This adhesive layer was designated as the first adhesive layer. The thickness of the first adhesive layer was 1.8 μm.
[0125] A 60 μm thick non-oriented polypropylene film (CPP) with one side corona treatment was prepared as the sealant layer. The surface of the intermediate film B on which the gas barrier coating layer was formed was bonded to the corona-treated surface of the sealant layer by dry lamination using a solvent-based adhesive A as the second adhesive layer. The thickness of the second adhesive layer was 3.5 μm. A laminate was obtained as described above.
[0126] Example 12 A transparent deposition layer (first inorganic oxide deposition layer) made of aluminum oxide and having a thickness of 10 nm was formed on the outer corona-treated surface of the base layer by a vacuum deposition device using an electron beam heating method. The O / Al ratio of the deposition layer was set to 1.8 by adjusting the type of deposition material. Other than this, the same procedure as in Example 11 was carried out to obtain a laminate.
[0127] Comparative Example 4 A laminate was obtained in the same manner as in Example 7, except that the first inorganic oxide vapor deposition layer was not formed.
[0128] Comparative Example 5 A laminate was obtained in the same manner as in Example 9, except that the first inorganic oxide vapor-deposited layer was not formed.
[0129] Comparative Example 6 A laminate was obtained in the same manner as in Example 11, except that the first inorganic oxide vapor deposition layer was not formed.
[0130] <Evaluation> The laminates of each example were subjected to the following evaluations, and the results are shown in Tables 1 and 2.
[0131] (Recyclability) The proportion (mass%) of polyethylene or polypropylene in the laminate of each example was calculated based on the above formula (1). In all examples, the content of polyethylene or polypropylene was 90 mass% or more.
[0132] (Evaluation of heat resistance) Two sheets of 10 cm square were cut out from the laminate, and the first inorganic oxide deposition layer side or the base material layer side was placed facing each other. In this state, the two sheets were sandwiched between PET films from above and below to prepare a sample for evaluation. Next, the sealing temperature of the top and bottom of the heat seal tester was set to 100 to 200°C, and heat was applied to the sample under the following conditions. Then, the surface welding temperature between the two sheets (the temperature at which the seal strength is 2N / 15mm or more) was compared with the lower limit sealing temperature of the sealant layer of each laminate. It can be said that the higher the surface welding temperature between the two sheets is and the larger the difference between the surface welding temperature between the two sheets and the lower limit sealing temperature of the sealant layer is, the more excellent the heat sealability is. -Sealing conditions- Heating times: 3 times, sealing time: 0.5 seconds, sealing waiting time: 0.5 seconds Number of cooling times: 3, Cooling time: 0.5s, Cooling standby time: 0.5s
[0133] (Bag making suitability evaluation) From the laminate in the form of a film roll, a bag making machine (manufactured by Totani Giken Kogyo Co., Ltd.) was used to make a self-supporting bag (standing pouch) consisting of a main body member and a bottom member folded in half so that the first inorganic oxide deposition layer side or the base material layer side faces each other. Then, the lower limit sealing temperature of the sealant layer and the surface welding temperature of the facing surface of the bottom member were confirmed, and the evaluation was performed according to the following criteria. ◯: The difference between the lower limit sealing temperature of the sealant layer and the above surface welding temperature was more than 20°C. ×: The difference between the lower limit sealing temperature of the sealant layer and the above surface welding temperature was 20° C. or less.
[0134] (Evaluation of visibility of contents) The packaging materials (packaging bags) produced in the above bag-making suitability evaluation had excellent visibility of the contents in all examples.
[0135] (Boiling and retort sterilization evaluation) A 15cm x 15cm three-sided pouch was made from the laminate (Example) that was evaluated as ◯ for bag-making suitability, and was filled with 100g of water as the content and then sealed. The laminate made of polyethylene was subjected to boiling treatment (treatment conditions: 95°C for 30 minutes), and the laminate made of polypropylene was subjected to retort treatment (treatment conditions: 121°C for 30 minutes, hot water storage type, pressure 0.2MPa), and the adhesion state of the sealant layer after the sterilization treatment was confirmed. Evaluation was performed according to the following criteria. ◯: No adhesion between the sealant layers was observed. ×: Welding between the sealant layers was observed.
[0136] [Table 1]
[0137] [Table 2]
[0138] As shown in Table 1, the laminates of the Examples were excellent in recyclability, heat sealability, and visibility of the contents, whereas the laminates of the Comparative Examples were poor at least in heat sealability. [Explanation of symbols]
[0139] Reference Signs List 1, 2: laminate, 10: substrate layer, 10a: outer surface of substrate layer, 10b: inner surface of substrate layer, 11: first inorganic oxide vapor-deposited layer, 12: printed layer, 14: second inorganic oxide vapor-deposited layer, 15: gas barrier coating layer, 20: intermediate layer, 30: sealant layer, 40: first adhesive layer, 50, 60: second adhesive layer.
Claims
1. A first inorganic oxide vapor-deposited layer, a base layer, and a sealant layer are laminated in this order, A laminate, wherein the substrate layer and the sealant layer both comprise polyethylene or both comprise polypropylene.
2. 2. The laminate of claim 1, further comprising an intermediate layer between the substrate layer and the sealant layer, the substrate layer, the intermediate layer and the sealant layer all comprising polyethylene or all comprising polypropylene.
3. The laminate according to claim 1 , wherein the substrate layer is a biaxially stretched film.
4. The laminate according to claim 2 , further comprising a second inorganic oxide vapor-deposited layer formed on the intermediate layer.
5. 3. The laminate according to claim 2, wherein the base layer and the intermediate layer are laminated together via a first adhesive layer, and the intermediate layer and the sealant layer are laminated together via a second adhesive layer, the second adhesive layer comprising a gas barrier adhesive.
6. 2. The laminate according to claim 1, wherein the ratio of polyethylene or polypropylene in the laminate is 90 mass % or more.
7. A packaging material comprising the laminate according to any one of claims 1 to 6.
8. The packaging material according to claim 7, which is a stand-up pouch.
9. A package comprising the packaging material according to claim 7 and contents contained in the packaging material.
Citation Information
Patent Citations
Multilayer structures, processes for manufacturing multilayer structures, and related articles
JP2020517502A
